View of the high plinth of the Chaunsath Yogini Temple - Temples of India Project Team (Jio Institute, 2024)
A closer view of the high plinth of the Chaunsath Yogini Temple is seen here. The plinth is composed of a pitha (base) on which are large kumbha (pot-shaped) wide projections, each having a devakoshtha (niche) on the surface. The mouldings of this plinth are similar to the mouldings of temple base plinth. A few plain bands are followed by a kapotali (cyma recta) moulding, kumbha, kalasha (a pitcher), and kani.